Kajian Materi Pendidikan Seni Musik Angklung - Teguh Gumilar (Journal on Education, 2024)
Angklung music education material has a variety of types that are adapted to the level of education and availability of angklung musical instruments. This research is about angklung music education material which is applied in non-formal learning and formal learning at elementary, middle school, high school and college levels. The aim of the research is to describe the educational material for the art of angklung music. The method used is the method in this article using library research, namely a method of collecting data by understanding and studying theories from various literature related to the research. The results of the research show that educational materials have different terms but have the same meaning, such as the terms teaching materials, learning materials, teaching materials and learning materials. The angklung music education material that is applied has benefits in students' musical intelligence, numeracy, love of local culture, and angklung playing skills.